STATUS MUTU PERAIRAN TELUK GORONTALO DENGAN MENGGUNAKAN METODE POLLUTION INDEX - Miftahul Khair Kadim; Nuralim Pasisingi (JFMR (Journal of Fisheries and Marine Research), 2018)
Water quality is very vital to support the survival of organisms. Determination of water quality status needs to be carried out as a reference for monitoring water pollution of an aquatic system. This study aims to assess the status of water quality in the Gorontalo Bay. There are 5 observation stations selected based on the coastal conditions and ecological characteristics. Sampling of water quality parameters was conducted along the Gorontalo Bay in May to July 2017. Sampling procedure based on APHA standard method. The water quality data are analyzed using Pollution Indeks method. Gorontalo Bay has Pollution Index average score of 4.74. This value shows that the quality status of the Gorontalo Bay is considered as polluted category.